Kurgusal Bir Karşı-İspanya: Sinapia ve İspanyol Ütopyası. - OKKA TAĞMAN, Ayşegül (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2026)
This study examines the concept of utopia within a theoretical and historical framework, analyzing its development in Spanish literature and, in particular, the place of the anonymous work Sinapia within this tradition. Utopia is considered not only a design for an ideal society but also an intellectual tool that criticizes the existing social order and possesses the potential for transformation. After outlining the transformation of modern utopian thought in Europe since the Renaissance, the study focuses on the unique character of Spanish utopia. In Spanish thought, utopia emerged not only as a fictional genre but also as a practical field intertwined with innovative projects linked to the New World experience. Sinapia, whose full title is Descripción de la Sinapia, península en la tierra austral, is central to this study and is considered a systematic example of utopia in Spanish literature. Discovered in 1975 in the archives of Count Campomanes, this text presents an ideal model of society reflecting the influences of Enlightenment thought. The work presents Enlightenment ideals through a fictional peninsula, contrasting them with the social and political realities of Spain. Sinapia is notable for its depiction of a society based on an equal ownership system and shaped by the people's understanding of virtue. This study challenges the common view that Spanish literature is underdeveloped in terms of utopian fiction; it positions Sinapia as both a continuation of the European utopian tradition and an original product of the reformist approach in Spanish thought. In this context, the work is re-evaluated not merely as an imaginary utopian design, but as a critical and transformative text directed at existing reality.